A National Survey of the Prevalence of Chronic Pain in Nursing Students and the Associated Factors - Shaygan, Maryam; Tehranineshat, Banafsheh; Mohammadi, Agrin; Foruhi, Zohreh (Investigación y Educación en Enfermería, 2023)
Objective. To examine the prevalence of chronic pain and the associated factors among nursing students. Methods. This study is a descriptive, cross-sectional. The subjects were 1684 nursing students who were selected from the universities of medical sciences in Iran via cluster sampling in 2019. Data were collected using a three-part questionnaire: a demographic characteristics survey, characteristics of chronic pain, and a pain scale. Results. The majority of the students were female (62.1%) and single (87%).The mean age of the participants was 22.4±2.96 years. The results of data analysis showed that 30.2% of the students suffered from chronic pain. The areas which were most affected by pain were: head (31.24%), abdomen (11.98%), and the back (9.23%). 56.4% of the nursing students declared the origin of their pain to be unknown, 22.7% attributed their pain to migraine, and 6.48% reported spinal disorders to be the cause of their pain. There was a significant relationship between the students’ chronic pain and the variables of age (higher in the 29-and-above age group), marital status (higher in married subjects), and education (higher in postgraduates). Conclusion. A relatively large number of nursing students suffer from chronic pains. Nursing schools should contribute to improving students' knowledge of chronic pain prevention and management.